Evidentiality in Abductive Reasoning: Experimental Support for a Modal Analysis of Evidentials. (9th November 2021) - Smirnova, Anastasia
Abstract: This paper presents results from two experimental studies that address a theoretical debate in semantics about the meaning of evidentiality and its relation to epistemic modality (Faller 2002 ; 2011 ; Izvorski 1997 ; Koev 2017 ; Lee 2013 ; Matthewson et al. 2007 ; McCready & Ogata 2007 ; Murray 2010 ; Smirnova 2013 ). According to modal analyses, evidentiality, in addition to the information source, encodes that the proposition in the scope of the evidential is possibly/necessarily true. Non-modal analyses postulate that evidential sentences entail the proposition in their scope and have the same semantic strength as non-evidential sentences. The predictions of the two approaches are tested for Bulgarian. In Study 1, I hold knowledge source—inference—constant and vary the type of logical argument, deductive versus abductive (cf. Lassiter & Goodman 2015 ; Douven & Verbrugge 2010 ). I find that evidential choices are influenced by both the type of the argument and the perceived subjective strength of the argument. In Study 2, I show that evidential and non-evidential sentences are associated with different degrees of certainty, where certainty can be viewed as an operationalization of semantic strength. These results are predicted by modal analyses but not by the non-modal view.